PENGEMBANGAN MODEL PEMBELAJARAN ETNOLINGUISTIK BERBASIS NILAI-NILAI ISLAM NUSANTARA UNTUK MAHASISWA PGSD - Murtono, Murtono; Ahsin, S.Pd., M.Pd., Muhammad Noor (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study was (1) to apply the ethnolingistic learning model based on Islamic values of the nusantara to students of Elementary School Teacher Education (PGSD). This research is development research. The stages in this study took seven steps from the ten R & D steps offered by Gall and Borg. The data to be collected in this study is data that shows the teaching material and design of ethnolinguistic learning based on Islamic Nusantara values for PGSD students. The product trial subjects were lecturers and PGSD students at Muria Kudus University. The results of this study are ethnolinguistic learning models based on Islamic values of the nusantara and teaching materials. Based on the results of the discussion it can be concluded that the ethnolinguistic learning model based on Islamic values of the nusantara and ethnolinguistic teaching materials based on Islamic values of the nusantara are appropriate and meet the requirements to be used as learning models and teaching materials.